Optimasi Remote Moderated Usability Testing Pada Low-Fidelity Prototype Dari E-Commerce Dengan Wawancara Pada Generasi Z Di Indonesia - Kelana, Bayu; L.R., Alya Firyal; Firmansyah, Frans; A, Khalisa Salma (Universitas Islam Syekh Yusuf, 2023)
The research aims to optimize the remote moderated usability testing on low-fidelity prototype of e-commerce with the interview among Indonesia’s generation Z. To achieve this objective, the research compares the number of negative findings from usability testing between remote moderated usability testing only and with additional interview. The usability testing was conducted online with think-aloud protocol, to five undergraduate students in Jabodetabek area, Indonesia. Qualitative data recorded in video, were observed, processed, and analyzed to obtain findings with negative sentiment. Usability testing with additional interview can increase the negative findings by 100%. Therefore, the interview technique significantly can be used to optimize the remote moderated usability among Indonesia’s generation Z.